Synthesis and Characterization of Polyurethane Nanocomposites - Puri, Pooja (Thapar University, 2016)
Current enthusiasm in the field of the nanotechnology leads to the development of nanocomposites as one of the rapidly evolving areas of composites research. Nanocomposites are multiphase materials, where one of the phases has nanoscale dimensions. Most nanocomposites composed of just two phases, one continuous phase called matrix and other nanophase dispersed in the matrix. The objective to fabricate such nanocomposite materials is to obtain distinct properties evolved from the synergistic effects of the component materials. This may include improved physical or chemical properties, enhanced environmental stabilities that may be exploited for various applications such as military equipments, safety, protective garments, automotive, aerospace, electronics and optical devices. At present, although nanocomposites employing CNTs as carbon based fillers are dominating but graphene and graphite nanoplatelets (GNPs) are considered to open a new area of functionalized nanocomposite systems in the near future. Graphene have high enormous surface area (up to 2630 m2 g-1), high aspect ratio (200–1500), and high electrical (106 (ohm cm)-1) and thermal (400W m-1 K-1) conductivities . GNPs are small stacks of graphene and exhibits similar exceptional properties to pure monolayer graphene sheet as well as CNTs. However, though the GNPs improve the electrical properties but there is not significant change in the mechanical properties of the prepared nanocomposites. Therefore, attempts were made to use a second filler with GNPs to retain/enhance the mechanical properties of PU along with its electrical properties. Using montmorillonite (MMT) clay to reinforce polymer-based composites have raised much attention to academic and industrial sectors due to the addition of small amount of clay could substantially enhance the mechanical properties of pristine polymers. Strong interfacial interactions between the dispersed clay layers and the polymer matrix lead to enhanced mechanical, thermal and barrier properties of the virgin polymer. The thesis entitled “Synthesis and Characterization of Polyurethane Nanocomposites” deals with the preparation of polymer graphite nanocomposites using GNPs and the montmorillonite clay as the nanofillers and polyurethane as the matrix material. Attempts have been made to synthesize composites using GNPs and polymers because the dispersion of GNPs in polymers shows various applications such as in solar cells, EMI shielding materials, LEDs, energy storage materials, electrochemical cells, sensors etc . The synthesis of polyurethane /organically modified montomoriillonite has also been attempted to study the effect of clay on mechanical properties of the nanocomposites. Finally, to study the synergic effect of both the fillers, GNPs and the clay in polyurethane, ternary nanocomposites based on GNPs, OMMT and polyurethane were prepared using in-situ polymerization. PU/OMMT (Polyurethane/Organically Modified Montmorillonite) nanocomposites were prepared by in situ polymerization Technique. The structure of prepared nanocomposites and dispersion state of filler was studied and characterized by XRD and TEM. An intercalation type of morphology was observed by TEM. The mechanical properties of these nanocomposites at different loading levels of OMMT were also investigated using the Universal testing machine. The tensile strength, elongation at break and hardness shore were enhanced with the increase in the loading level of OMMT as compared to pure polyurethane. The obtained properties may be used in MEMS applications like pressure diaphragm, where the mechanical properties on nanoscale are crucial. Further, the incorporation of GNPs was attempted in polyurethane. The polyurethane/graphite composites have been synthesized with the aim of using them for electromagnetic shielding applications. The polyurethane/graphite composites were prepared through in situ polymerization method in the presence of graphite nanoparticles. The prepared composites were characterized by scanning electron microscope, transmission electron microscope (TEM), and x-ray diffraction techniques. The shifting of the major peak of GNPs in prepared nanocomposites towards the left from 26.336 (d-spacing = 3.381 Å ) to 25.374 (d-spacing = 3.507 Å ) a 2θ scale indicates the intercalation type of dispersion in the prepared nanocomposites. This was further validated with the TEM characterization. The introduction of GNPs in PU during in situ polymerization creates an electrical network in the resulting composite, which therefore makes it highly conductive. The prepared nanocomposite showed an electrical network at 2.2 vol.% of the percolation threshold in DC condition and a similar percolation threshold was found at 100 Hz in AC conditions. The maximum conductivity found at 6.5 vol.% of filler loading was 0.01 S/cm. The resulting composites were evaluated for electromagnetic interference (EMI) shielding at different filler loadings. The prepared PU/GNPs composites were found to be highly effective with shielding effectiveness of 19.34 dB, and with electromagnetic interference shielding materials at 0.9–1 GHz. Finally, to study the synergic effect of both the fillers, GNPs and the clay in polyurethane, ternary nanocomposites based on GNPs, OMMT and polyurethane were prepared using in-situ polymerization with the aim of achieving low percolation threshold and improving the electrical and mechanical properties. The nanocomposites were evaluated for their electrical and mechanical properties and the results were compared with the corresponding binary systems, i.e., PU having GNP as the only filler. It was observed that the addition of OMMT at a concentration of around 2 wt%, significantly enhances the electrical and mechanical properties of the nanocomposites with the percolation threshold at much lower concentration of the GNPs. The excellent electrochemical properties arise due to formation of new 3D network (clay-graphite-clay or graphite-clay-graphite) and the synergistic effect between the three components.
PHD, SCBC
Keywords: Composite Materials; Polyurethane; Graphite Nanoparticles; Percolation Threshold; MEMS; SCBC